The Outcomes of Primary Debulking Surgery and Neoadjuvant Chemotherapy in Advanced Ovarian Cancer - Dino Rinaldy; Andrijono Andrijono; Bambang Sutrisna (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To compare the outcomes and survival rate of primary debulking surgery with neoadjuvant chemotherapy. Method: We selected advanced ovarian cancer patients from medical records. Subjects were allocated into groups of primary debulking surgery and neoajuvant chemotherapy by considering the inclusion and exclusion criteria. We analyzed the data using T test, Fisher’s exact, and chi-square. The survival rate was presented in Kaplan Meier curve, whereas the significance was tested with Logrank. We managed the data using STRATA software version 12. Result: We obtained 32 cases of primary debulking surgery group and 20 cases of the neoadjuvant chemotherapy group. Most of the subjects (44.2%) were 40-49 years old and 80.8% had delivered more than twice. The mean value of Ca-125 at admission was 3,594.8 u/ml (range 66.6 to 73,000 u/ml). Total of 31 subjects showed the serous histologic type (59.6%). There was no association between primary debulking surgery and neoadjuvant chemotherapy for the parameter of operative time, blood loss, organs injury, ICU stay, and hospital stay (p>0.05). Primary debulking surgery had a survival rate similar to neoadjuvant chemotherapy group (p=0.95). Conclusion: The perioperative outcomes of advanced ovarian cancer patients has similar result between primary debulking surgery and neoadjuvant chemotherapy. Primary debulking surgery has a survival rate similar to neoadjuvant chemotherapy group. [Indones J Obstet Gynecol 2016; 4-2: 111-115] Keywords: advanced ovarian cancer, neoadjuvant chemotherapy, primary debulking surgery